Comparative study of extended free‐volume defects in As‐ and Ge‐based glassy semiconductors: theoretical prediction and experimental probing with PAL technique. Issue 1 (5th December 2012) - Shpotyuk, Oleh; Golovchak, Roman; Ingram, Adam; Boyko, Vitaliy; Shpotyuk, Lyubov
Abstract The role of spatially‐extended defect configurations in As‐Se and Ge‐Se glasses is identified using available theoretical predictions and positron annihilation lifetime spectroscopy as an experimental tool. It is shown that compositional trends in average positron lifetime do not coincide with molar volume evolution in the glasses of corresponding binary systems. The heteropolar As‐Se covalent bonds are shown to affect the positron trapping modes more efficiently, than geometrical voids responsible for compositional deviation in molar volume. The same tendency is observed for Se‐rich Ge‐Se glasses. However, the Ge‐rich glasses in so‐called pseudo‐self‐organization domain, demonstrate an opposite trend in a favour of molecular clustering of edge‐ and corner‐shared tetrahedral units. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)